Procopius and the Persian Wars - Greatrex, G; Greatrex, G. (1994)
﻿ This thesis takes as its focus book I of Procopius' Persian Wars in an attempt to investigate both the events it describes and the way in which they are reported. A two-fold approach has therefore been employed, on the one hand dealing with the actual events, and on the other with Procopius' handling of them compared to that of other sources. While the first chapter thus considers Procopius himself and the genre of 'classicising' history, the second provides the fifth-century background to the events. Subsequent chapters generally consider the events in question first, before going on to examine Procopius' account in detail. The third chapter investigates Procopius' information on Sasanian history and the Hephthalite Huns, which is remarkably detailed. The following chapter considers his account of the war waged against the Persians under the Emperor Anastasius (502-506), and concludes that he is offering a very partial account. Chapters five and six consider the centrepiece of Persian Wars I: the campaigns of 530 and 531, including Belisarius' victory at Dara and defeat at Callinicum. Close comparison with the chronicler John Malalas is undertaken in the case of the latter battle. Chapter seven analyses Procopius' excursus into southern Arabian affairs. where he seems to have had access to good geographical and historical information. Chapter eight considers the final events reported in Persian Wars I, which, it is argued, were added at a later stage; his account of the Nika riot in Constantinople is omitted from consideration, but his final detailed excursus on internal Persian history and his report on the coup at Dara are examined. A conclusion is offered at the end, emphasising the general accuracy of Procopius, particularly concerning events of his own day, and seeking to account for his selectiveness in the deployment of information.